Optimal cooling strategies for players in Australian Tennis Open - Lynch, G. P.; Pierard, J. D.; Pluim, B. M.; Brotherhood, J. R.; Jay, O. (Journal of Science and Medicine in Sport, 2018)
Objectives: We compared the utility of four cooling interventions for reducing heat strain during simulatedtennis match-play in an environment representative of the peak conditions possible at the Australian Open (45°C, <10% RH, 475 W/m2 solar radiation). Design: Nine trained males undertook four trials in a climate chamber, each time completing 4 sets ofsimulated match-play. Methods: During ITF-mandated breaks (90-s between odd-numbered games; 120-s between sets), eithericed towels (ICE), an electric fan (FAN dry), a fan with moisture applied to the skin (FAN wet), or ad libitum10°C water ingestion only (CON) was administered. Rectal temperature (T re), mean skin temperature(T sk), heart rate (HR), thermal sensation (TS), perceived exertion (RPE) and whole body sweating (WBSR) were measured. Results: After set 3, T re was lower in ICE (38.2+-0.3.°C) compared to FANdry(38.7 +- 0.5°C; p = 0.02) and CON (38.5 +- 0.5°C; p = 0.05), while T re in FAN wet (38.2 +- 0.3°C) was lower than FAN dry (p = 0.05). End-exercise T re was lower in ICE (38.1 +- 0.3°C) and FAN wet(38.2 +- 0.4°C) than FAN dry(38.9 +- 0.7°C; p < 0.04) and CON (38.8 +- 0.5°C; p < 0.04). T sk for ICE (35.3 +- 0.8°C) was lower than all conditions, and T sk for FAN wet (36.6 +- 1.1°C) was lower than FAN dry (38.1 +- 1.3°C; p < 0.05). TS for ICE and FAN wet were lower than CON and FAN dry (p < 0.05). HR was suppressed in ICE and FAN wet relative to CON and FAN dry (p < 0.05). WBSR was greater in FAN dry compared to FAN wet (p < 0.01) and ICE (p < 0.001). Conclusions: Fan use must be used with skin wetting to be effective in hot/dry conditions. This strategy and the currently recommended ICE intervention both reduced T re by ~0.5- 0.6°C and T sk by ~1.0- 1.5°C while mitigating rises in HR and TS.